Development of PAIKEM-Based Buddhist Education Teaching Materials in Class IV Elementary Schools - Puskainah, Puskainah; Yamin, Martinis; Emosda, Emosda (Program Magister Teknologi Pendidikan Universitas Jambi, 2022)
Develop teaching materials based PAIKEM (Active, Innovative, Creative, Effective and Fun Learning) Buddhist education. The purpose of this development is to produce teaching materials based PAIKEM Buddhist education can improve student learning outcomes and fit for use for educational learning Buddhism. The model of development adopted development model by Dick & Carey. Broadly speaking, this development model consists of 9 phases: 1) Identify Instructional Goals, 2) Conduct Instructional Analysis, 3) Identify Entry Behaviors and Learner Characteristics, 4) Write Performance Objectives, 5) Develop Criterion-Referenced Test Items, 6) Develop Instructional Strategy, 7) Develop and Select Instructional Materials, 8) Develop and Conduct Formative Evaluation, 9) Develop and Conduct Summative Evaluation. Product testing conducted on fourth grade students at Citra Nusantara Elementary School, Jambi. Based on the validation results of teaching materials, the overall form teaching materials can be categorized as good and fit for use in Buddhist education